Exploring Teacher's Identity in EFL Classroom: A Personal Reflection - Armin Fani (ENLIT, 2022)
Abstract The importance of teacher identities catches the interest of many scholars. teacher identities are part teacher development as educator. The priority in education has been shifted to maximize the effectiveness of teacher role through developing their identity. Thus, it is a worth conducting a research which investigates. (1) What identity are constructed by teacher in English teaching learning process? (2) What are the factors that influence teacher’s identity construction? The trajectory of this study was conducted through narrative inquiry research principles. The participants of this study were a teacher of one private university in Banjarmasin. To collect the data, semi-structured interview was administered. The collected data was analyzed through data familiarizing, decoding, and presenting the data. Finally, the result was presented descriptively. The finding of this study reveals type teacher identities in English language teaching. The data show that teacher identities includes language related identity, disciplinary identities, and context related identities. The data also show that the construction of teacher identities determines by teacher experience during teaching career and practiced-knowledge identity. Teacher experience develop through teacher trajectory of teaching. Meanwhile practiced-teaching skill cover language knowledge and pedagogic knowledge that teacher employ to help conducting effective teaching.